The Influence of Recruitment, Selection, and Training on Employee Productivity at PTPN III Kebun Sisumut Labuhanbatu South - Tengku Irwansyah Putra; Aziddin Harahap; Abd. Halim (Budapest International Research and Critics University, 2023)
Globalization creates intense competition in various fields. In order to win the competition, companies are starting to compete and are required to get competent human resources to be able to support the progress of their business and be able to compete with other companies. This study analyzes the influenceRecruitment, Selection, and Training on Employee Work Productivity in the company, considering the important role of human resources in the company's competitive advantage. The purpose of this writing is to find out how far the development of research related to this topic. The method used in this study is an exploratory approach by reviewing the contents or identifying several articles from both national and international journals. The research results show that either simultaneously or partially it proves that the Recruitment, Selection, Training system has a significant effect on Work Productivity. Simultaneously Recruitment, Selection, and Training affect the Work Productivity of PTPN III SISUMUT Labuhanbatu Selatan Regency by obtaining an Fcount of 22, 141 and a significance level of 0.000. So that human resource management plays an important role in the realization of quality employees and has optimal work productivity.